Exploring mergers and acquisitions in public accounting - McGowan, J.; Norris, D. (International Journal of Accounting & Business Finance, 2023)
Mergers and acquisitions (M&A) assist public accounting firms in multiple ways. These transactions expand client services, open opportunities in consulting and wealth management, increase revenues, and secure talented personnel. This exploratory study looks to build a preliminary model surrounding the likelihood a firm participates in an M&A transaction. To do so, a sample of the top 100 accounting firms, as reported by Accounting Today in 2019, is utilized. This data is combined with hand-collected news reports of mergers or acquisitions that occurred in 2018. Utilizing logistic regression, the effects of different firm characteristics such as revenues, CEO gender, and management efficiency on the likelihood of a public accounting firm being involved in a merger or acquisition are presented. The model is significant, having a log likelihood of 74.65. This study contains limitations. As this study’s sample is confined to the top 100 firms and reflects a short time window, these results might not apply to all accounting firms. Further, not all accounting firms’ M&A transactions are public knowledge, which may result in a biased sample. However, these limitations do not prevent this study from providing value. This study is one of the few to explore M&A transactions in public accounting. As certain firm characteristics are found to be related to M&A activity, this paper provides a starting point for future research on this topic at a time when M&A activity in public accounting is gaining in popularity.
Keywords: Mergers and Acquisitions; Public Accounting; Human Capital; Consolidation